Identificação de barreiras para a escolarização inclusiva de alunos com deficiências físicas - Teixeira, Emanuele (2009)
In recent years, studies on the efficiency and practices based on policies of school inclusion have presented results often controversial. The lack of concrete data has been considered the main difficulty encountered in the accurate assessment of how this process has been occurred. The few systematic studies related to this topic have been restricted to individual testimonies and experiences, unable to assess the impact of policy on practice in schools. As a result, studies to improve the quality of education and, thus, promote access to these students, have been necessary. In this way, the actual work aimed to conduct a study using a descriptive method to promote inclusive education of students with disabilities in common schools, through the identification and description of barriers encountered by these students. To identify such barriers, data were collected from interviews with students from three different cities, using a specific instrument for this purpose ( The School-Setting Interview 3.0 SSI ), which was translated and adapted to Brazilian reality. The participants were 24 students with disabilities, between 7 to 16 years old, actually educated in regular education classes of regular teaching from three different cities (A, B and C). The results were analyzed to identify possible variation in the number and types of barriers depending on the city, gender, education level and motor impairment, in addition to access of assistance. Qualitative analysis was performed to identify and exemplify personalized barriers encountered by students in specific situation. Results showed that these cities, which were subject to the same general laws, have very different initiatives regarded to school inclusion. As the barriers faced by students, data showed that adjustments are being made in schools, although the number and variety of barriers faced by these students is still concern, and that policies of school inclusion need to be more effective. Moreover, it is concluded that, in students perception, the social barriers overcome the physical ones, since there is a greater investment in adapting the physical environment, which involves costless attitudes that could be implemented in short period of time, while the engagement against social and educational barriers, which would require more expensive and more structural alternatives, is still considerably being ignored.